Kontroversi Tanggal Wafat Imam Ali Ra dan Tinjauannya dalam Perspektif Astronomi Islam - Nadirin, Akhmad (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2022)
Ali bin Abi Talib is one of the companions of the Prophet SAW who is guaranteed to enter heaven along with nine other friends. He led Islam for about four years before being stabbed by Abdurrahman bin Muljam while praying shubuh at the end of 40 AH until he died. In some literature, Imam Ali was killed on Friday night or Sunday night. In addition, there are several opinions in various Islamic historical literature about the date of the death of Ali ibn Abi Talib. Some say on Friday, 17 Ramadan 40 H. There are also opinions that mention 11 Ramadan 40 H. Some even write that Imam Ali died at the end of Rabiul Awal 40 H. This research is intended to answer the problem of Imam Ali's death date in perspective. astronomy. This problem is discussed with qualitative research in the form of library research. The primary source used in this study is T?rikh al-T?bari T?rikh al-Um?m w? alMuluk, Ash?b al-Futuy? , al-K?mil fi al-T?rikh, al-Bid?y?h w? al-Nih?y?h. All the data obtained were then converted into either the day or the date of the Gregorian era and matched the data in the historical book. The results showed that the data on the date of the death of Ali bin Abi Talib based on astronomical calculations was on Sunday, 17 Ramadan 40 H / 24th January 661 AD.Keywords: controversy, date of death, Imam Ali ra, astronomy